Teaching motor skills by means of biomechanical analysis of the motion: the physiological basis and applied information technologies - Razuvanova A.V.; Koshelskaya E.V.; Karpova I.A.; Medvedeva E.V. (SHS Web of Conferences, 2016)
The article proves the possibility of training athletes using motor skills on the basis of biomechanical analysis of movements with application of information technologies. Motion Tracking – digital single frame shooting photography – is proposed as a method for biomechanical analysis. The relevance of this method is conditioned by the results of the study of a repulsion phase in the performing of the standing jump by athletes of different qualifications. The conclusion about the importance of an optimal model of a jump based on biomechanical analysis is given, and the formation of athletes’ skills, using information technologies and the principle of urgent information, is discussed.